1996
DOI: 10.1212/wnl.47.6.1504
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from nonfluent aphasia after melodic intonation therapy

Abstract: We examined mechanisms of recovery from aphasia in seven nonfluent aphasic patients, who were successfully treated with melodic intonation therapy (MIT) after a lengthy absence of spontaneous recovery. We measured changes in relative cerebral blood flow (CBF) with positron emission tomography (PET) during hearing and repetition of simple words, and during repetition of MIT-loaded words. Without MIT, language tasks abnormally activated right hemisphere regions, homotopic to those activated in the normal subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
222
2
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(238 citation statements)
references
References 35 publications
11
222
2
3
Order By: Relevance
“…The compensatory role of the right hemisphere was also the focus of several recent activation studies which in fact showed that in the end spared regions of the left hemisphere were the main substrate of recovery mechanisms. In the same vein, Belin et al (19) and Warburton et al (415) proposed that persistent activations in the right hemisphere could even compromise the restoration of language functions in the left hemisphere. The critical impact of the level of activity in the left superior temporal cortex for recovery was repeatedly stressed by Heiss and his group.…”
Section: Language Recovery Poststrokementioning
confidence: 99%
See 1 more Smart Citation
“…The compensatory role of the right hemisphere was also the focus of several recent activation studies which in fact showed that in the end spared regions of the left hemisphere were the main substrate of recovery mechanisms. In the same vein, Belin et al (19) and Warburton et al (415) proposed that persistent activations in the right hemisphere could even compromise the restoration of language functions in the left hemisphere. The critical impact of the level of activity in the left superior temporal cortex for recovery was repeatedly stressed by Heiss and his group.…”
Section: Language Recovery Poststrokementioning
confidence: 99%
“…Belin et al (19) were the first to address the relationships between specific language therapy in aphasia and neural reorganization explored with PET. These authors focused on speech production and observed better performance in patients who displayed left-sided perilesional activations after melodic intonation therapy.…”
Section: Language Recovery Poststrokementioning
confidence: 99%
“…Singing mainly relies on right hemispheric function and can help people with left hemispheric lesions produce speech by bypassing the injured hemisphere [40]. Learning a list of words in a song activates frontal and temporal brain areas on both sides of the brain while spoken-word learning activates only areas in the left hemisphere [41].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625mentioning
confidence: 99%
“…Prior to the publication of that report, some researchers reported significant activation of the right frontal cortex on functional imaging in non-fluent aphasic patients, and commented that over-activation in the right hemisphere might impede the functional reorganization of the left hemispheric language circuits that are necessary for the recovery of language function (i.e., a maladaptive response) (Belin et al, 1996;Rosen et al, 2000). Therefore, Naeser et al hypothesized that neural suppression of the over-activated right hemisphere by inhibitory low-frequency rTMS can lead to language functional recovery, by reducing interhemispheric inhibition from the right hemisphere towards the left hemisphere.…”
Section: What Is Therapeutic Rtms After Stroke?mentioning
confidence: 99%